Characterisation of the pharmacodynamic effects of the P2X7 receptor antagonist JNJ-54175446 using an oral dexamphetamine challenge model in healthy males in a randomised, double-blind, placebo-controlled, multiple ascending dose trial. (September 2020) - Recourt, Kasper; van der Aart, Jasper; Jacobs, Gabriel; de Kam, Marieke; Drevets, Wayne; van Nueten, Luc; Kanhai, Kawita; Siebenga, Pieter; Zuiker, Rob; Ravenstijn, Paulien; Timmers, Maarten; van Gerven, Joop; et al.
Background: This is the first report of the pharmacodynamic (PD) effects of the selective, potent and brain-penetrant P2X7 receptor (P2X7R) antagonist JNJ-54175446. Activation of the P2X7R, an adenosine triphosphate-gated ion channel, leads to the production of pro-inflammatory cytokines, which have been linked to neuroinflammation and play a role in the pathogenesis of mood disorders. Previous clinical studies with JNJ-54175446 demonstrated peripheral target engagement of JNJ-54175446 by assessing ex vivo lipopolysaccharide (LPS)-stimulated cytokine production. Blood–brain barrier penetration and a clear dose–receptor occupancy relationship was demonstrated using positron emission tomography. Aims: The objectives of this double-blind, placebo-controlled, translational study were to assess the safety and tolerability of administering multiple doses of JNJ-54175446 and to explore its PD effects using a dexamphetamine challenge. Methods: Subjects ( N  = 64) were randomised to either JNJ-54175446 (50–450 mg; n  = 48) or placebo ( n  = 16) and underwent a baseline oral 20 mg dexamphetamine challenge followed by 11 consecutive days q.d. dosing with JNJ-54175446/placebo and a randomised crossover dexamphetamine/placebo challenge. Results: At all doses tested, JNJ-54175446 was well tolerated and suppressed the ex vivo LPS-induced release of cytokines. At doses ⩾100 mg, JNJ-54175446 attenuated dexamphetamine-induced increases in locomotion and enhanced the mood-elevating effects of dexamphetamine, suggesting that a dose that is approximately twice as high is needed to obtain a central PD response compared to the dose needed for maximum peripheral occupancy. Conclusion: Overall, the observed pharmacological profile of JNJ-54175446 in the dexamphetamine challenge paradigm is compatible with a potential mood-modulating effect.